Prospective ex-ante life cycle assessment of an emerging resource recovery solution based on food waste - Haodong Lin; Isabela Butnar; Aiduan Borrion (The International Journal of Life Cycle Assessment, 2026)
Purpose Emerging technologies facilitate the circular economy transition by converting waste into value-added products. Environmental assessments of these technologies are increasingly gaining attention; however, scaling up remains a major challenge, leading to significant data gaps. To address this issue, this study applied an ex-ante LCA to a resource recovery solution integrated with an emerging technology, comparing three upscaling approaches: simple extrapolation, process engineering modelling, and approximation. Methods The ex-ante LCA was conducted in accordance with ISO 14,040 and 14,044 standards to evaluate the environmental impacts of the resource recovery solution, integrating an emerging digestate valorisation technology into a conventional anaerobic digestion plant. Life cycle inventories were compiled from a UK anaerobic digestion plant and the upscaled technology, applying the three upscaling approaches. Four near-future scenarios were developed: a business-as-usual case and three scenarios based on the respective upscaling methods. Five impact categories relevant to digestate production and management were evaluated: climate change, fine particulate matter formation, terrestrial acidification, fossil resource scarcity, and water use. Additionally, long-term future scenarios were established by adopting projected future background data, considering shared socioeconomic pathway 2, representing a middle-of-the-road development trajectory. Results and discussions Results show that, compared to the business-as-usual case, the resource recovery solution reduced more than 46% impacts in climate change, terrestrial acidification, and water use, primarily due to the avoided digestate storage and using recovered water. However, fine particulate matter formation and fossil resource scarcity impacts vary across upscaling methods. The process engineering modelling method demonstrated the best overall environmental performance, followed by approximation and simple extrapolation approaches. The long-term future scenario confirmed potential for improvements across all selected impact categories by 2050. Sensitivity analysis identified key parameters, including emission factors, recovery efficiencies, economic values of products, and upscaling factor. Conclusions This study applied ex‑ante LCA to assess the environmental impacts of a resource recovery solution and compared three upscaling methods to examine their influence on results. The findings underscore the importance of method selection, comprehensive impact assessment, and high‑quality data. Future work should include uncertainty and broader sustainability analysis. Overall, the study advances ex‑ante LCA by demonstrating how multiple upscaling approaches can address data gaps in bio‑waste resource‑recovery technologies and support early decision‑making in the anaerobic digestion sector.

Sustainability of bioenergy – Mapping the risks & benefits to inform future bioenergy systems - Andrew James Welfle; Alberto Almena; Muhammad Naveed Arshad; Scott William Banks; Isabela Butnar; Katie Jane Chong; SamuelJ.G. Cooper; Helen Daly; Samira Garcia Freites; Fatih Güleç; Christopher Hardacre; Robert Holland; et al. (Biomass and Bioenergy, 2023)

Carbon accounting of negative emissions technologies integrated in the life cycle of spirulina supplements - Ana Fernández-Ríos; Isabela Butnar; María Margallo; Jara Laso; Aiduan Borrion; Rubén Aldaco (Science of The Total Environment, 2023)

Wasting Food, Wasting Resources: Potential Environmental Savings Through Food Waste Reductions - Arkaitz Usubiaga; Isabela Butnar; Philipp Schepelmann (Journal of Industrial Ecology, 2018)
Summary Food is needed to maintain our physical integrity and therefore meets a most basic human need. The food sector got in the focus of environmental policy, because of its environmental implications and its inefficiency in terms of the amount of food lost along the value chain. The European Commission (EC) flagged the food waste issue a few years ago and adopted since then a series of policies that partially address the problem. Among these, the Resource Efficiency Roadmap set the aspirational goal of reducing the resource inputs in the food chain by 20% and halving the disposal of edible food waste by 2020. Focusing on consumer food waste, we tested what a reduction following the Roadmap's food waste target would imply for four environmental categories in EU28 (European Union 28 Member States): greenhouse gas emissions, land use, blue water consumption, and material use. Compared to the 2011 levels, reaching the target would lead to 2% to 7% reductions of the total footprint depending on the environmental category. This equals a 10% to 11% decrease in inputs in the food value chain (i.e., around half of the resource use reductions targeted). The vast majority of potential gains are related to households, rather than the food‐related services. Most likely, the 2020 target will not be met, since there is insufficient action both at Member State and European levels. The Sustainable Development Goals provide a new milestone for reducing edible food waste, but Europe needs to rise up to the challenge of decreasing its per capita food waste generation by 50% by 2030.

A comparison of the GHG emissions caused by manufacturing tissue paper from virgin pulp or recycled waste paper - Eskinder Demisse Gemechu; Isabela Butnar; Jordi Gomà-Camps; Alfred Pons; Francesc Castells (The International Journal of Life Cycle Assessment, 2013)